SLANG WORDS IN RIHANNA’S SONG LYRICS: SOCIOLINGUISTIC APPROACH - Handayani, Nurma Dhona; Silalahi, Deasy Sartika (LPPM Universitas Putera Batam, 2019)
Language is known as a communication tool that is very important for a human being to convey messages, opinions or ideas. Sociolinguistics is a science that discuss about language seen from the society. Slang word is a kind of language variety which is informal and use in a society. The purpose of this research is to analyze word formation and find out social functions of slang words in Rihanna's song lyrics. This research is kind of qualitative research. In the process of collecting data, researcher used observation method. Moreover, Pragmatic Identity method with dividing key-factors technique was used to analyze data of this research. After analyzing the collected data, it can be seen the types of word formation which were used in Rihanna’s song lyrics. There were 37 data found from Rihanna’s songs. The data were divided into 5 types of word formation in Slang word found in Rihanna’s song lyrics. Those types were coinage 1 data, blending 10 data, clipping 19 data, acronym 3 data and the last prefixes and suffixes 1 data. It can be concluded that there were many slang words used in Rihanna’s song lyric.